2021
DOI: 10.3390/cells10092250
|View full text |Cite
|
Sign up to set email alerts
|

Epitranscriptomic Approach: To Improve the Efficacy of ICB Therapy by Co-Targeting Intracellular Checkpoint CISH

Abstract: Cellular immunotherapy has recently emerged as a fourth pillar in cancer treatment co-joining surgery, chemotherapy and radiotherapy. Where, the discovery of immune checkpoint blockage or inhibition (ICB/ICI), anti-PD-1/PD-L1 and anti-CTLA4-based, therapy has revolutionized the class of cancer treatment at a different level. However, some cancer patients escape this immune surveillance mechanism and become resistant to ICB-therapy. Therefore, a more advanced or an alternative treatment is required urgently. De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 201 publications
(221 reference statements)
0
4
0
Order By: Relevance
“…The knockdown of CISH may regulate the metabolic activity of NK cells to exert an anti-tumor effect [ 40 , 41 ]. In addition, a previous study has shown that the inhibiting of CISH could improve the outcomes of immune checkpoint blockade therapy [ 42 ]. The existing study has confirmed that HERC4 is involved in inhibiting the proliferation of myeloma cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of CISH may regulate the metabolic activity of NK cells to exert an anti-tumor effect [ 40 , 41 ]. In addition, a previous study has shown that the inhibiting of CISH could improve the outcomes of immune checkpoint blockade therapy [ 42 ]. The existing study has confirmed that HERC4 is involved in inhibiting the proliferation of myeloma cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The co-targeting of cell surface immune checkpoint proteins (PD1 and PDL1) along with intracellular checkpoint molecules such as CISH is a promising approach [ 12 ], and might improve the results of ICIs in TNBC. Our objective was to document CISH expression in a large series of TNBC clinical samples and to search for correlations with tumor features and an eventual synergy with PDL1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all patients derive benefit from these ICIs dedicated to improving antitumor cytotoxic immune responses, and many patients develop resistance to these treatments. These limitations emphasize the need to identify new cells and molecules that could be exploited in the next generation of immunotherapy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kumar and colleagues contributed a new approach to improve the efficacy of ICI therapy by co-targeting molecular machineries involved in the modifications of specific RNA to overcome toxicities and drug resistance to antibodies to immune-checkpoint receptors. That epitranscriptomics and general epigenetic molecular mechanisms can play an essential role in determining the cell fate in development and differentiation is becoming increasingly clear [ 11 ]. Joyce Taylor-Papadimitriou and Joy M. Burchell have clearly shown the changes occurring in cancer determined by histone methylases and demethylases [ 12 ].…”
Section: Autoimmunity and Antitumor Responsementioning
confidence: 99%